2020
DOI: 10.1037/pspp0000262
|View full text |Cite
|
Sign up to set email alerts
|

Owner of a lonely heart: The stability of loneliness across the life span.

Abstract: Individuals feel lonely when they perceive a discrepancy between their aspired and their actually experienced amount of closeness and intimacy in social relationships. In the present study, we disentangled developmental constancy factors, time-varying factors such as person-environment transactions, and stochastic mechanisms as sources of interindividual differences in loneliness by applying STARTS models in nationally representative samples from Germany (n = 13,397), Switzerland (n = 6,599), Australia (n = 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 115 publications
(291 reference statements)
4
38
0
2
Order By: Relevance
“…We set the stable trait variances for both variables to 0.25, autoregressive trait variances to 0.55, and occasion-specific state variances to 0.2. These variance proportions are in line with findings from longitudinal research that applied the univariate STARTS model (Jansen et al, 2020;Mund et al, 2020; see also Usami, Todo, & Murayama, 2019). The total variance of the manifest variables was set to 1.…”
Section: Simulation Model and Conditionssupporting
confidence: 86%
See 1 more Smart Citation
“…We set the stable trait variances for both variables to 0.25, autoregressive trait variances to 0.55, and occasion-specific state variances to 0.2. These variance proportions are in line with findings from longitudinal research that applied the univariate STARTS model (Jansen et al, 2020;Mund et al, 2020; see also Usami, Todo, & Murayama, 2019). The total variance of the manifest variables was set to 1.…”
Section: Simulation Model and Conditionssupporting
confidence: 86%
“…This has been applied to constructs such as life satisfaction (Lucas & Donellan, 2007;Schimmack et al, 2010), academic self-concept (Jansen et al, 2020), self-esteem (Alessandri et al, 2016;Donellan et al, 2012;Wagner et al, 2016), loneliness (Mund et al, 2020), and personality traits (Anusic et al, 2012;Anusic & Schimmack, 2016).…”
Section: Univariate Starts Modelmentioning
confidence: 99%
“…Moreover, it seems that the individuals who are classified as "lonely" based on cut-off scores on multi-item scales are not the same individuals who are classified as "lonely" based on the same cut-off score applied to single-item measures (Eccles et al, 2020;Shiovitz-Ezra & Ayalon, 2012). Apart from prevalence rates, however, the results obtained with single-item measures converge very well with those obtained with multi-item scales with regard to demographic aspects (Shiovitz-Ezra & Ayalon, 2012;von Soest et al, 2020), aspects of mean-level and rank-order stability (Mund, Freuding, et al, 2020;Mund, Lüdtke, et al, 2020), interpersonal dynamics (Mund & Johnson, 2021;Mund et al, in press), personality correlates (Buecker et al, 2020), and health outcomes (Beutel et al, 2017;Eccles et al, 2020), including early mortality (Holt-Lunstad et al, 2015;Shiovitz-Ezra & Ayalon, 2010).…”
Section: Single Items and Multi-item Scalesmentioning
confidence: 76%
“…Russell, 1982). In line with this reasoning, a study employing STARTS models (Kenny & Zautra, 2001) found that single item measures capture more (potentially unreliable) state variance (≈ 50% state variance) than longer scales such as a 6-item version of the RTLS (≈ 25% state variance; Mund, Lüdtke, et al, 2020). However, it has been shown for single-item measures of subjective well-being that state variance can contain a substantial amount of reliable variance (Lucas & Donnellan, 2012).…”
Section: Single Items and Multi-item Scalesmentioning
confidence: 94%
“…The occasion-specific factor displays the time-varying part of agreeableness at any specific assessment point. Time-varying factors could be internal (e.g., changing genetic effects), external (e.g., environmental effects) or consequence from interactions between internal and external factors (Mund et al, 2020). The autoregressive coefficient indicates sustainability between consecutive occasion factors over time, reflecting relative influences of prior occasion factors on inter-individual differences in agreeableness at the next wave.…”
Section: Introductionmentioning
confidence: 99%